Kajian Dampak Penambangan Pasir Terhadap Kualitas Air Sungai Untuk Irigasi di Indonesia - Fahima, Sahidatun; Tanjung, Jeane Claudea; Sinatrya, Azka; Wulan, Indah Retno; Ngadisih, Ngadisih; Lestari, Prieskarinda (Universitas Tanjungpura, 2024)
The high demand for sand as a material is in line with the increase in sand mining activities. The main sand mining location commonly takes place in rivers. Even though rivers are also used as the main source for agricultural irrigation. The sand mining activities could affect river water quality, which could also impact irrigation on plant growth and crop yields. This review aimed to analyze the impact of sand mining in several locations in Indonesia on river water quality for irrigation. The data collection method was carried out by searching for articles according to the topic on Google Scholar using several predetermined keywords. Analysis and review were carried out through several stages and 6 articles were obtained according to the topic. Sand mining activities in rivers are frequently carried out using manual and mechanical techniques. The use of manual techniques in mining can have an impact on river morphology as well as the physical and chemical quality of river water. Mechanical techniques have a greater impact on changes in river water quality, where most mining is carried out using manual techniques. Therefore, the sand mining with mechanical techniques, especially using excavators, can have a higher impact on the quality of river water for irrigation.